In an hour, 80 people could ride the ferris wheel. So, that means in 3 hours 240 people could ride it.
Answer:
1. 49a^6b^10
2. −81a^8b^2c^2
Step-by-step explanation:
N/A
Answer:
![\huge\boxed{y-3=-\frac{1}{2}(x-1)}](https://tex.z-dn.net/?f=%5Chuge%5Cboxed%7By-3%3D-%5Cfrac%7B1%7D%7B2%7D%28x-1%29%7D)
Step-by-step explanation:
Point-slope is:
![y-y_1=m(x-x_1)](https://tex.z-dn.net/?f=y-y_1%3Dm%28x-x_1%29)
![m-\text{This represents the slope.}\\\\(x_1,y_1)-\text{This represents the point used in the equation.}](https://tex.z-dn.net/?f=m-%5Ctext%7BThis%20represents%20the%20slope.%7D%5C%5C%5C%5C%28x_1%2Cy_1%29-%5Ctext%7BThis%20represents%20the%20point%20used%20in%20the%20equation.%7D)
<h2>
Our goal: </h2>
We have to complete the point-slope equation of the line through (1,3) (5,1).
--------------------------------------------------------
We have a incomplete equation of the line.
![y-3=m(x-x_1)](https://tex.z-dn.net/?f=y-3%3Dm%28x-x_1%29)
We need to find the <u>slope</u> of the line, and the <u>value</u> of
.
--------------------------------------------------------
<h3>Finding 'x1':</h3>
It seems that the value of 3 was used to be
. This means that the point
was used for the equation. This means that
would have to be 1.
<h3>Finding Slope:</h3>
Slope is rise over run.
![m=\frac{rise}{run}=\frac{y_2-y_1}{x_2-x_1}](https://tex.z-dn.net/?f=m%3D%5Cfrac%7Brise%7D%7Brun%7D%3D%5Cfrac%7By_2-y_1%7D%7Bx_2-x_1%7D)
We are given the points (1,3) and (5,1).
![m=\frac{1-3}{5-1}=\frac{-2}{4}=\frac{-1}{2}=\boxed{-\frac{1}{2}}](https://tex.z-dn.net/?f=m%3D%5Cfrac%7B1-3%7D%7B5-1%7D%3D%5Cfrac%7B-2%7D%7B4%7D%3D%5Cfrac%7B-1%7D%7B2%7D%3D%5Cboxed%7B-%5Cfrac%7B1%7D%7B2%7D%7D)
The slope is one-half.
--------------------------------------------------------
We now have enough information to complete the point-slope equation.
![{\left \{ {{x_1=1} \atop {m=-\frac{1}{2} }} \right.}\\\\y-3=m(x-x_1)\rightarrow\boxed{y-3=-\frac{1}{2}(x-1)}](https://tex.z-dn.net/?f=%7B%5Cleft%20%5C%7B%20%7B%7Bx_1%3D1%7D%20%5Catop%20%7Bm%3D-%5Cfrac%7B1%7D%7B2%7D%20%7D%7D%20%5Cright.%7D%5C%5C%5C%5Cy-3%3Dm%28x-x_1%29%5Crightarrow%5Cboxed%7By-3%3D-%5Cfrac%7B1%7D%7B2%7D%28x-1%29%7D)
Our final equation is:
![y-3=-\frac{1}{2}(x-1)](https://tex.z-dn.net/?f=y-3%3D-%5Cfrac%7B1%7D%7B2%7D%28x-1%29)
Answer:
no
Step-by-step explanation: